IMPROVEMENT OF STUDENT LEARNING OUTCOMES THROUGH RECIPROCAL TEACHING APPROACH ASSISTED BY MIND MAP AT SCIENCE LEARNING IN JUNIOR HIGH SCHOOL - NURUL AZIZAH, ALFIA; BUDIYANTO, MOHAMMAD (PENSA E-JURNAL: PENDIDIKAN SAINS, 2019)
The research was conducted to describe the improvement of student learning outcomes towards the application of reciprocal teaching approach assisted by mind map at science learning in junior high school. This type of research was Pre-experimental with a sample of 35 students at VIII-A class in SMP Negeri 17 Surabaya. The research design which used was One Pretest-Posttest Group. The results of the study were published student learning outcomes sheets. The results showed that the mastery of learning posttest questions was 83%. Based on the t-test data analysis showed a significant difference before and after using reciprocal teaching approach assisted by mind map. Improved learning outcomes based on n-gain analysis were high 60%, moderate 37%, and low 3%.The research results of implementing reciprocal teaching approach assisted by mind map at science learning in junior high school shows an increase in learning outcomes. Keywords: learning outcomes, reciprocal teaching, mind map